Pengujian Toksisitas dan Antioksidan Ekstrak Etilasetat dan n-Butanol Hipokotil Sarang Semut, Myrmecodia pendens Merr. & Perry - Vino Soaduon Hamonangan Simanjuntak; Endah Wydiastuti; Lina Marlina; Partomouan Simanjuntak; Rudi Kartika (JURNAL KIMIA MULAWARMAN, 2023)
Sarang semut, Myrmecodia pendens Merr. & Perry (Rubiaceae) is an epiphytic plant from Papua which is used to cure various diseases. The purpose of this study is to see the chromatogram profile [Thin Layer Chromatography (TLC) and High Performance Liquid Chromatography (HPLC)] analysis, and biological test of ethyl acetate and n-butanol of Sarang semut’s hypocotyl extracts from methanol extracts. Meanwhile, the biological tests carried out were toxicity tests on Artemia salina L shrimp larvae and antioxidant assay with free radical scavenging methods (DPPH). The results of the antioxidant activity test showed that the antioxidant activity of the ethyl acetate extract was higher (IC50=18.23μg/ml) than the n-butanol extract (IC50=29.58μg/ml). The results of the toxicity test on the ethyl acetate extract were higher (LC50=101.84 g/ml) than the n-butanol extract (LC50=154.59 g/ml). TLC analysis results showed that the mobile phase for the best separation of chemical compounds in ethyl acetate extract was chloroform-methanol (10:1) and n-butanol extract was the mobile phase chloroform-methanol-water (5:5:1), while HPLC analysis showed that the mobile phase for the separation of chemical compounds in the ethyl acetate extract was n-hexane-ethyl acetate (10:1) and the n-butanol extract was methanol-water (10:1).